Evaluating Sharia Compliant Healthcare Standards: A Quantitative Study on Patient Satisfaction in Indonesian Hospitals - Fini Fajrini; Arif Sumantri; Andriyani Andriyani; Nur Hidayah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Management and services of Sharia hospitals require high quality institutional standards covering organization, human resources, facilities, services, and financial systems designed in accordance with Islamic Sharia principles. This study aims to empirically examine the effect of implementing these Sharia hospital standards on patient satisfaction in Indonesia, where faith based expectations significantly influence healthcare experiences. Methods: This quantitative study employed a Structural Equation Modeling Partial Least Squares (SEM-PLS) approach based on primary data. A total of 195 respondents were selected through purposive sampling from two certified Sharia compliant hospitals in Indonesia, Tangerang City Hospital and RSI Sari Asih Serang. Results: Bivariate analysis revealed significant relationships between all five Sharia hospital standard domains and patient satisfaction. Multivariate analysis, however, identified that only the facilities variable had a statistically significant effect, highlighting the central role of religiously congruent infrastructure. Conclusion: This study provides new empirical insights into the implementation of Sharia hospital standards by demonstrating that certified facilities enhance patient satisfaction particularly through physical environments that align with Islamic values. These findings contribute to the development of culturally responsive healthcare policies in Muslim majority settings.